Humic Substances as Indicator of Sustainable Crop Management Practices of Ultisols in Southern China - Bocar Ahamadou; Qiaoyun Huang; Lin Yaping; Javed Iqbal (Research Highlights in Agricultural Sciences Vol. 6, 2022)
Long-term fertilization can influence both organic C sequestration as well as the C composition of soils and the more resistant organic C compounds contained in humic acid (HA). Humic substances are extremely important attributes of soil quality but the effects of long-term fertilization on their chemical and spectroscopic characteristics remain controversial and are still not fully understood. To clarify the impact of long-term fertilisation practises on the composition and structure of humic substances, a study using a variety of methodologies was carried out. At the Red Soil Experimental Station of the Chinese Academy of Agricultural Sciences, soil samples were taken from eight treatments. The MSTAT-C software programme was used to perform an analysis of variance (ANOVA) on the data. Globally, bands between humic fractions could be distinguished by Fourier transform infrared (FT-IR) spectra. The humic acid (HA) from the NPK plus manure (NPKM) and manure alone (M) treatments showed higher values of the O/R ratios (1.24 and 1.18, respectively) as compared to that from the 1.5 NPKM and fallow (H) treatments, which decreased these ratios (0.66 and 0.85, respectively). Except for NPKM plus wheat- soybean-sweet potato between the lines (NPKMR), the O/R ratios of the fulvic acid (FA) did not differ among the treatments. However, the humin (HM) from H and the control (CK) displayed the highest value of O/R ratios (about 3.23 for both). Humic substances from organic treatments showed more aliphatic nature, whereas more condensed-alkali soluble humic substances were formed in the unfertilized and mineral treatments. Among fractions, the HA formed more phenolic or aromatic structures than did the FA or HM. Additionally, humic substances’ carbon, hydrogen, nitrogen, and sulphur contents significantly increased while their oxygen contents decreased. Significant correlations between the molecular make-up of humic substances and organic treatments were found. As a result, the characterization of humic substances may be used as a sign of how sustainable crop management techniques are over the long term. Foreseeing the future in this area can also be achieved through approach of coupling long-term experiments and modeling, since significant relationships were observed between the molecular composition of humic substances and organic treatments. Humic substances characterization could be also used as an indicator of the long-term sustainability of soil and crop management practices.